Production characteristics of Small East African goats and their crosses with Anglo-Nubian and Alpine under station conditions in semi-arid 'Bugesera' region of eastern Rwanda - Murayi, T.; Sayers, A.R.; Wilson, R.T. (1987)
The production characteristics of Small East African goats and their crosses are investigated under semi-arid conditions of Rwanda. The crossbreds were those of Small East African goat x Anglo-Nubian and Small East African x Alpine goats. Comparative data on reproductive performance, growth, weight, mortality and productivity indices included.